ALASAN PEREMPUAN MEMILIH PRINSIP MURABAHAH SEBAGAI PRODUK UNGGULAN BANK SYARIAH MANDIRI - RAHIM, ABDUL (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2014)
Housing finance (KPR), one of the leading products held by the Bank Syariah Mandiri has many devotees especially women. Based on the writer?s analysis, the reason underlying the high demand of women make housing finance is for the future of their families. Most of Bank Syariah Mandiri in Indonesia in general provide housing finance as a favorite product for women than many other products. In addition, another interesting product for women is automobile finance for buying a new car or a second hand one. Automobile finance is not many as housing finance.